Upgrading Romanian Cities with the EU Financial Assistance - Marchis, Gabriela (Acta Universitatis Danubius. Œconomica, 2022)
Romania can make a huge leap in development in the coming years using EU financial assistance, which is around 80 billion euros over the next 7 years. These funds will come through Cohesion Policy, the National Recovery and Resilience Plan and other European instruments. This paper highlights the funding opportunities for the 2021-2027 programming period, that a city benefits from, the aim of the paper being to create an integrated vision on the type of investments and actions that are needed in order to build a smart future for Romanian cities. The transition to a clean, circular economy and the stimulation of the efficient use of resources in urban areas in the long run can only be achieved through strong cooperation between local public actors and other urban actors, from the private or non-profit environment. Thus, this paper offers a long-term development vision on how to transform the Romanian cities in accordance with the current requirements of society, the intended implication being to raise awareness of all the stakeholders about their potential involvement in developing successful projects for their community so as not to miss any chance of development.